Traditional techniques for the rehabilitation and protection of historic earthen structures: The seismic retrofitting project - Lourenço, Paulo B. (2019)
Historic earthen structures are a significant portion of the built heritage worldwide and are associated with intangible building techniques, wide material availability and low-cost construction. Nonetheless, dueto their low mechanical properties and, often poor connections, historic earthen structures are susceptible to early structural damage, and even collapse in areas of high seismic hazard. Inaddition, the lack of maintenance can further reduce structural performance and durability. The Getty Conservation Institute (GCI)'s Seismic Retrofitting Project (SRP) aims to research, designand test low-tech retrofitting techniques, as well as to implement maintenance programs, enhancing the performance of historicearthen buildings in seismic areas where the most advanced equipment, structural skills and materials are not easily available. Results: Accounting for recommendations from national building codes, conservation principles and local practices, the complete design, assessment and implementation of strengthening for twoprototype buildings in Peru, involved in the SRP, are discussed; the Church of Kuno Tambo and Ica Cathedral. Conclusions: Theretrofitted structures, complied with performance criteria and seismic local demands, with sufficient safety and acceptable levels of repairable damage.